Recovery of mouse growth hormone from E. coli inclusion bodies using a mild solubilisation and repeated freeze–thaw approach - Minah Kim; Ries J. Langley; Jo K. Perry; Yue Wang (Molecular Biology Reports, 2025)
Background Recombinant mouse GH (mGH) is a critical tool for investigating GH-GH receptor (GHR) interactions in rodent models. However, while numerous methods exist for producing human GH, detailed protocols for the expression and purification of recombinant mGH remain scarce in the literature. Methods We developed a method for refolding mGH from inclusion bodies produced in Escherichia coli ( E. coli ). Recombinant mGH was fused with a N-terminal thioredoxin (Trx) tag and was expressed as inclusion body proteins in E. coli when induced at 30 °C. Inclusion bodies were isolated and solubilised under mild conditions (50 mM Tris–HCl, 2 M urea, pH 10.5) and freeze-thawed. Results Three rounds of freeze-thawing improved solubilisation when compared to a single round. Subsequently, recombinant mGH underwent Trx-tag removal and was purified using anion exchange chromatography to achieve a purity of 98%. Purified mGH displayed circular dichroism spectral profiles comparable to that of commercially sourced mGH, confirming the preservation of the secondary structure in refolded mGH. Bioactivity was confirmed using a Ba/F3-mGhr cell viability assay and showed that refolded mGH had comparable bioactivity to commercially sourced mGH. Bioactivity was also assessed by measuring activation of mGH receptor signal transduction in B16-F10 mouse melanoma cells by phosphorylated STAT5 western blot analysis. Conclusions We present an efficient and cost-effective protocol for mGH production. This repeated freeze–thaw approach may have broad application for other proteins expressed in the form of inclusion bodies for which low yields are observed following a single round of freeze–thaw.

First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

Temporal niche partitioning as a potential mechanism for coexistence in two sympatric mesopredator sharks - Neil D. Cook; Abbie Jenkins; Sarah L. Perry; Sarah E. Perkins; Jo Cable (Frontiers in Marine Science, 2024)
Global marine biodiversity declines require bold and ambitious plans to safeguard ecosystem services. Overfishing, habitat loss and projected climate impacts have yielded deleterious effects on marine predators, in particular, driving increasing threat of extinction for many shark species with implications for ecosystem health. Identifying and protecting critical habitat areas for sharks is fundamental to their protection, and may allow for species recovery. Here we use baited remote underwater video stations to investigate spatial and temporal patterns of habitat use by sharks in a Special Area of Conservation (SAC) that is centrally important to the regional blue economy in the UK, the Cardigan Bay SAC. Our results show heterogeneous spatial habitat use and temporal trends in habitat sharing between smallspotted catsharks Scyliorhinus canicula and nursehounds S. stellaris . Nearshore reef habitats are substantially more important than non-reef habitats for both species. The relative abundance of each species, however, is roughly inversely seasonally proportional, with S. canicula and S. stellaris relative abundance highest in March and September, respectively. Temporal niche partitioning may be an important mechanism in marine systems, but has not been widely investigated in sympatric shark communities. These findings are directly relevant for ongoing development of the Welsh Marine Evidence Strategy (2019-2025) and the Welsh National Marine Plan, particularly to inform spatial planning to strengthen the role of SAC management design in protecting important shark areas.

An international ecological study of adult height in relation to cancer incidence for 24 anatomical sites - Yannan Jiang; Roger J. Marshall; Sarah C. Walpole; David Prieto-Merino; Dong-Xu Liu; Jo K. Perry (Cancer Causes & Control, 2015)

Acute anxiety increases the magnitude of the cold shock response before and after habituation - Martin James Barwood; Jo Corbett; Richard Green; Tim Smith; Perry Tomlin; Lydia Weir-Blankenstein; Michael J. Tipton (European Journal of Applied Physiology, 2013)

Molecular distinction between true centric fission and pericentric duplication-fission - Jo Perry; Sara Nouri; Phung La; Art Daniel; Zhanhe Wu; Stuart Purvis-Smith; Emma Northrop; K. H. Andy Choo; Howard R. Slater (Human Genetics, 2005)

Chromosome size and origin as determinants of the level of CENP-A incorporation into human centromeres - Danielle V. Irvine; David J. Amor; Jo Perry; Nicolas Sirvent; Florence Pedeutour; K. H. Andy Choo; Richard Saffery (Chromosome Research, 2004)

Centric fission — simple and complex mechanisms - Jo Perry; Howard R. Slater; K. H. Andy Choo (Chromosome Research, 2004)

In vivo and in vitro swelling of cell walls during fruit ripening - Robert J. Redgwell; Elspeth MacRae; Ian Hallett; Monica Fischer; Jo Perry; Roger Harker (Planta, 1997)